Timeline of an attack. Issue 9 (September 2016) - Burdette, Phil
Abstract : What can you accomplish in 314 days? That's how long it took one intrepid pilgrim to walk from Bosnia to Mecca, while yachtsman Matt Rutherford completed a circumnavigation of the Americas in the same time. It's also how long scientists expect the trip to Mars to take. Mankind can indeed achieve great things in a little over 10 months – but sadly, noticing a data breach is not among them, with most successful corporate attacks going unnoticed for an average of 314 days.